Circular RNA circSLC7A11 contributes to progression and stemness of laryngeal squamous cell carcinoma via sponging miR-877-5p from LASP1 - Wenjie Yu; Xiaoling He; Chunming Zhang; Fuhui Huang (Heliyon, 2023)
Background: Laryngeal squamous cell carcinoma (LSCC) belongs to tumors of head and neck. Circular RNA circSLC7A11 functions as oncogenes in various tumors. However, the role of circSLC7A11 in LSCC remains largely unknown. Here, we aimed to clarify the circSLC7A11 function in LSCC. Methods: Relevance between circSLC7A11 expressions and LSCC clinicopathological was checked using chi-square. Relevance between circSLC7A11 expressions and LSCC patients' survival time was validated using Kaplan-Meier analysis. CircSLC7A11 expressions in LSCC tissues and cells were determined using quantitative real-time PCR. CircSLC7A11 functions in LSCC were examined by Cell Counting Kit-8, EdU analysis, Western blot, flow cytometry, sphere formation assay, and Transwell analysis. Meanwhile, circSLC7A11 mechanism in LSCC was determined using dual-luciferase reporter analysis, RNA pull-down, RNA Immunoprecipitation. Results: CircSLC7A11 was highly expressed in LSCC, and high circSLC7A11 expressions were interrelated to the TNM stage. Also, LSCC patients with high circSLC7A11 owned shorter overall survival. Functional studies revealed that circSLC7A11 knockdown reduced LSCC cell proliferation, migration, invasion, stemness characteristics, and enhanced cell apoptosis. Mechanistic study data corroborated that circSLC7A11 targeted miR-877-5p, miR-877-5p targeted LASP1. LASP1 was negatively interrelated to miR-877-5p and was positively interrelated to circSLC7A11 in LSCC tissues. Also, circSLC7A11 knockdown reduced the LASP1 levels, and miR-877-5p inhibitor co-transfection reversed this reduction. Rescue assays further demonstrated that circSLC7A11 accelerated LSCC through miR-877-5p/LASP1. Conclusion: CircSLC7A11 exerted oncogenic functions in LSCC by miR-877-5p/LASP1, hinting that circSLC7A11 was a novel biomarker for LSCC.